(3TQM fgL GdHdGZIs - (3CHh MGeO YRGdOjf YHO GdMejO Hf gHg Gddg Hf eMeO Hf GdMSjf Hf CHi GdMOjOs; (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdYOd adeG egO CQVg , hGfa(B> (3CeQg , GNJGQ BOe Ydjg GdSdGe s
(3BNQgG (B:s
(3acja EPG GfVGa Edi YOe GddPI GdeJfGgjI MUhd eVGQ hYbhHGJ ZjQ eJfGgjI hGdMeO ddg s
(3cJHgG CcKQ ef fGSNs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
Keywords: (3GdCOHs